Green spaces, excess weight and obesity in Spain - O'Callaghan-Gordo, Cristina; Espinosa, Ana; Valentin, Antonia; Tonne, Cathryn; Pérez-Gómez, Beatriz; Castaño-Vinyals, Gemma; Dierssen-Sotos, Trinidad; Moreno-Iribas, Conchi; de Sanjose, Silvia; Fernandez-Tardón, Guillermo; Vanaclocha-Espi, Mercedes; Chirlaque, María Dolores; et al. (International journal of hygiene and environmental health, 2020)
The epidemiological evidence on green spaces and obesity is inconsistent. To study the association of access to green spaces and surrounding greenness with obesity in Spain. We enrolled 2354 individuals 20–85 years from urban areas of seven provinces of Spain between 2008–13. Subjects were randomly selected population controls of the MCC-Spain case-control study. We geocoded current residences and defined exposures in a buffer of 300 m around them: i) access to green space, identified using Urban Atlas, and ii) levels of surrounding greenness, measured by the Normalized Difference Vegetation Index. We examined excess weight/obesity as binary outcomes based on body mass index and waist-hip ratio. We examined effect modification by genetic factors, sex and individual socio-economic status and mediation by physical activity and concentrations of PM2.5 and NO2. To assess potential effect modification by genetic factors, we used a polygenic risk score based on obesity polymorphisms detected in genome-wide association studies. We used logistic mixed-effects models with a random effect for catchment area adjusted for potential confounders. Access to green space was associated with a reduced risk of excess weight/obesity after adjusting for confounders [excess weight: OR (95%CI) = 0.82 (0.63, 1.07), p-value = 0.143; abdominal obesity: OR (95%CI) = 0.68 (0.45, 1.01), p-value = 0.057]. In the stratified analysis, this association was only observed in women. Associations between surrounding greenness and excess weight/obesity were null or modest based on a 1 IQR increase in NDVI [excess weight: OR (95%CI) = 0.99 (0.88, 1.11), p-value = 0.875; abdominal obesity: OR (95%CI) = 0.91 (0.79, 1.05), p-value = 0.186]. The observed associations were not mediated by physical activity or air pollution. Access to green space may be associated with decreased risk of excess weight/obesity among women in Spain. Mechanisms explaining this association remain unclear.